Penerapan Algoritma Rabin-Public Key Untuk Pengamanan File Audio - Rusdianto Rusdianto; Natalia Silalahi; Norenta Sitohang (Bulletin of Artificial Intelligence, 2023)
Data encoding problems such as text files, images, audio and video are used more often as messages or information. However, with advances in technology that are increasingly developing, it is increasingly possible for messages or information to be stored in the form of other files such as images, audio and video. For example, a music recording company wants to release the latest album and they want to get a big profit from selling CDs or downloading legally (paid) through the site. Before the album officially goes out to the public, they want to make sure that no one party gets a leak or listens to the audio file first. One of the technical solutions that can be used to protect the confidentiality of audio files is cryptography by applying the Rabin-Public Key algorithm. The Rabin-p algorithm is an algorithm that implements an asymmetric key. An asymmetric key is a key that uses two types of keys, namely the public key which is used to encrypt the message and the secret key which is used to decrypt the message. Rabin-p is named rabin with an additional p which symbolizes that the proposed scheme uses only one prime p as the decryption key. The results for encoding audio files are based on an asymmetric cryptographic system that uses a public key and a private key for encoding audio files (the key used for the encryption process). and decryption) into a cipher so that the security and confidentiality of messages are maintained. Audio file analysis is the stage where analysis is carried out on any files that are processed in a design system or procedure, in this case the audio files to be encrypted and decrypted in cryptographic applications are audio files in wave format (*.WAV).